MOLECULAR CHARACTERIZATION OF SOLUBLE AND MEMBRANE‐BOUND TREHALASES IN THE COTTON MIRID BUG, Apolygus lucorum. Issue 2 (16th April 2014) - Tan, Yongan; Xiao, Liubin; Sun, Yang; Zhao, Jing; Bai, Lixin; Xiao, Yingfang
<x xml:space="preserve">Abstract</x> Trehalose, a major hemolymph sugar in insects, is hydrolyzed by trehalase. We identified a soluble and a membrane‐bound form of trehalase and isolated the corresponding mRNA, ALTre‐1, and ALTre‐2 in the cotton mirid bug, Apolygus lucorum. The deduced amino acid sequences of ALTre‐1 and ALTre‐2 revealed mature proteins with 643 and 617 amino acids, respectively. ALTre‐1 and ALTre‐2 contained trehalase signature motifs, and ALTre‐2 contained a putative transmembrane domain near the C‐terminus, suggesting that ALTre‐1 and ALTre‐2 encoded a soluble trehalase and a membrane‐bound trehalase, respectively. Comparison of trehalase activity at different developmental stages and in six tissues indicated that soluble trehalase activity accounted for the majority of total trehalase activity in A. lucorum. ALTre‐1 and ALTre‐2 were expressed in all tissues and stages, with the highest expression of both in the second instar nymphs, ALTre‐1 in the ovary and malpighian tubules, ALTre‐2 in the flight muscles and fat body. Following the exposure of second instar nymph to 20‐E, the soluble trehalase activity increased gradually while the membrane‐bound trehalase activity remained at its initial level. Similarly, 20‐E upregulated ALTre‐1 expression but had no effect on ALTre‐2 expression. These results suggest that an increase of this soluble trehalase activity was upregulated by ALTre‐1 gene.